2015
DOI: 10.3390/socsci4041162
|View full text |Cite
|
Sign up to set email alerts
|

Who Benefits from Public Healthcare Subsidies in Egypt?

Abstract: Direct subsidization of healthcare services has been widely used in many countries to improve health outcomes. It is commonly believed that the poor are the main beneficiaries from these subsidies. We test this hypothesis in Egypt by empirically analyzing the distribution of public healthcare subsidies using data from Egypt Demographic and Health Survey and Egypt National Health Accounts. To determine the distribution of public health care subsidies, we conducted a Benefit Incidence Analysis. As a robustness c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 20 publications
(30 reference statements)
0
39
0
Order By: Relevance
“…In addition to the lack of financial means, the poor also benefit less from public subsidies to the health sector than the better‐off. In a recent study, Rashad and Sharaf () found evidence that public healthcare subsidies in Egypt are in general pro‐rich and have inequality increasing effect, particularly subsidies associated with university hospitals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the lack of financial means, the poor also benefit less from public subsidies to the health sector than the better‐off. In a recent study, Rashad and Sharaf () found evidence that public healthcare subsidies in Egypt are in general pro‐rich and have inequality increasing effect, particularly subsidies associated with university hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…The demand for maternity healthcare is mainly served by private health providers that require fees, as public health service is widely viewed as an inferior service. The reliance on private healthcare in Egypt was found to be pushing a substantial proportion of households into poverty and deprivation (Rashad & Sharaf, , ).…”
Section: Discussionmentioning
confidence: 99%
“…Rashad and Sharaf, like other authors in this collection, stress the importance of equity to the health of communities and society at large [20]. The findings of their quantitative study in Egypt reject the hypothesis that health care subsidies mostly benefit the poor.…”
mentioning
confidence: 71%
“…A possible justification for the lower access to health care among the poor is the unequal distribution of health workforce and the domination of private maternal care that requires user fees and could derive poor and near poor households into financial catastrophe (Rashad & Sharaf, 2015b, 2015a. In addition, there is an empirical evidence of a pro-rich distribution of public healthcare subsidies in Egypt (Rashad & Sharaf, 2015d).…”
Section: Discussion and Policy Implicationsmentioning
confidence: 99%